THE EFFECT OF COMMUNICATIVE LANGUAGE TEACHING (CLT) METHOD ON ENGLISH COMPREHENSION FOR STUDENTS AT THE FIFTH GRADE OF SD KARTIKA X-3 - Naya, Kartyca; Katemba, Caroline V. (Journal of Language Pedagogy, 2011)
This study incolves the students at the fifth grade of SD Kartika X-3 as the subject of the research.Â And the writer teaches them through Information Gap, games, Pair Work, et cetera. A pre and post test was administered. The data was analyzed by suing t-test.Â The result shows that studentsâ English comprehension had improved by using Communicative Language TGeaching (CLT) method at the coefficient t counted =2265>t table = 1667 with the significance of level in 0.05 and the degree freedon is 32 (df=n-1).Â The studentsâ responses toward the post-test given prove that Communicative Language Teaching (CLT) method is effective to improve studentsâ English comprehension ability.